POLA ASUH ORANG TUA TERHADAP ANAK BERKEBUTUHAN KHUSUS YANG BERPRESTASI DI SLB NEGERI 1 TANJUNGPINANG TIMUR - Maya Rifqi Nasution; Siti Arieta; Sri Wahyuni (JURNAL SOSIO-KOMUNIKA, 2023)
Parenting is a method or way to educate, love and facilitate children in an effort to shape the child's identity. Every parent certainly has differences in providing care, especially for children with special needs. The purpose of this study was to determine the forms of parenting and motivation used by parents for children with special needs to become outstanding children at SLB Negeri 1 Tanjungpinang Timur. The method used in this research is a qualitative method with a descriptive method approach. The data sources used are in the form of observation, interview and documentation data. Structured interview data is obtained based on interview guidelines. The theory used in this research is Talcot Parson's Functional Structure Theory. Parenting consists of three categories, namely authoritarian parenting, permissive parenting and democratic parenting. The results showed that parents of children with special needs in the application of parenting use a democratic approach because children are given freedom, there is no coercion and selfishness of parents to children so that children are more optimal in choosing their abilities in achieving at SLB Negeri 1 Tanjungpinang Timur